The role of local government in the process of entrepreneurship development - Tomasz Skica; Agnieszka Bem; Karolina Żygadło (e-Finanse: Financial Internet Quarterly, 2013)
This article presents the role of local governments in supporting entrepreneurship development. The content of the article presents the factors which foster activities undertaken by local authorities to promote entrepreneurship and also shows different considerations of when the supporting instruments are in use. The article is also an assessment of current activities of local governments in the sphere of supporting business initiatives. It indicates potential of possible changes in local policy on supporting entrepreneurship. The article sets out areas of possible improvements in policy when stimulating economic activity by local authorities. It addresses the improvements of the objective restrictions which are laid out by the existing legal framework.
Keywords: H7; H8; 330; entrepreneurship; local government; supporting entrepreneurship; SMEs; local development